The Behavior of Unemployment Durations over the Cycle - Dynarski, Mark; Sheffrin, Steven M. (The Review of Economics and Statistics, 1990)
This paper examines the relationship between unemployment durations and cyclical movements in unemployment using an "employment calendar" constructed from recent questions in the Panel Study of Income Dynamics. We find that unemployment durations increase with the unemployment rate with the strongest effects for individuals with the longest elapsed durations. Copyright 1990 by MIT Press.